Challenges of school leaders’ digital leadership: An initial study in Bintulu, Sarawak, Malaysia - Adhi Masri Yeop Johari; Muhammad Faizal A. Ghani; Norfariza Mohd Radzi; Amalina Ayub; Maszuria A. Ghani (Faculty of Education, Universitas Negeri Yogyakarta, 2023)
Technological development is constant and rapid. These changes involve not only communication, the economy, or the health field but also education. To overcome these issues, school leaders are required to equip themselves with the knowledge of the digital field. Therefore, this study explores the challenges or issues that school leaders face. In order to achieve the goals of this study, the data were collected by applying a qualitative method using a case study approach through semi-structured interviews. Two school leaders participated in the interview session.Â Thematic analysis was used to sort out the data in order to determine the themes. This study found that the issues in school leadersâ€™ digital leadership are lack of knowledge, inability to use data for school planning, lack of computers and devices for teaching and learning activities, and lack of engagement. The implication of this study is to make education stakeholders, such as school leaders, aware of the importance of digital leadership in school.